2019
DOI: 10.1002/jcb.27830
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐9 overexpression suppresses vulnerable atherosclerotic plaque and enhances vascular remodeling through negative regulation of the p38MAPK pathway via OLR1 in acute coronary syndrome

Abstract: Acute coronary syndrome (ACS) is characterized by atherosclerotic plaque rupture with a high incidence of recurrent ischemic events. Several microRNAs are found to be aberrantly expressed in atherosclerotic plaques. This study aims to investigate the effects of microRNA‐9 (miR‐9) on vulnerable atherosclerotic plaque and vascular remodeling in ACS and underlying mechanisms. Microarray‐based gene expression profiling was used to identify differentially expressed genes related to ACS and regulatory miRNAs. Oxidiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…A recent study has reported that the over-expression of miR-150 maintains the function of endothelial cells and suppresses VR by inhibiting pentraxin-3 (PTX3) expression, as well as activation of the NF-κB signaling pathway in ACS mice ( Luo et al, 2018 ). Moreover, up-regulated miR-9 is known to suppress the formation of vulnerable atherosclerotic plaques and enhance VR in ACS mice through negative-regulation of the p38MAPK pathway via OLR1, while our findings indicate a similar function via inhibition of the FAK/ERK signaling pathway ( Yu et al, 2020 ). Over-expression of miR-9 in bone marrow-derived mesenchymal stem cells is also known to diminish the levels of IL-6, IL-1β, and TNF-α in acute pancreatitis, highlighting the critical role of miR-9 up-regulation in inhibition of inflammatory responses ( Qian et al, 2017 ).…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…A recent study has reported that the over-expression of miR-150 maintains the function of endothelial cells and suppresses VR by inhibiting pentraxin-3 (PTX3) expression, as well as activation of the NF-κB signaling pathway in ACS mice ( Luo et al, 2018 ). Moreover, up-regulated miR-9 is known to suppress the formation of vulnerable atherosclerotic plaques and enhance VR in ACS mice through negative-regulation of the p38MAPK pathway via OLR1, while our findings indicate a similar function via inhibition of the FAK/ERK signaling pathway ( Yu et al, 2020 ). Over-expression of miR-9 in bone marrow-derived mesenchymal stem cells is also known to diminish the levels of IL-6, IL-1β, and TNF-α in acute pancreatitis, highlighting the critical role of miR-9 up-regulation in inhibition of inflammatory responses ( Qian et al, 2017 ).…”
Section: Discussionmentioning
confidence: 55%
“…Moreover, significantly diminished expression of miRNAs such as miR-17, miR-126, and miR-155, has been previously documented in patients with coronary artery disease ( Izawa and Amano, 2015 ). Besides that, Yu et al (2020) observed poor miR-9 expression in n the aortic tissue of mice with atherosclerosis. miRNAs possess the ability to modulate gene expression post-transcriptionally by comprehensively interacting with the 3’UTR of specific target mRNAs ( Ivey and Srivastava, 2015 ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…8 In addition, another study suggests miR-9 suppresses vulnerable atherosclerotic plaque in acute coronary syndrome mice. 9 microRNA-139-5p (miR-139-5p) has been previously known as being aberrant regulated in some cardiac ischemia/reperfusion models. 10 miR-139-5p has also been reported to restrain isoproterenol-induced cardiac hypertrophy.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study indicates that up‐regulated miR‐377 partly relieves the progress of AS 8 . In addition, another study suggests miR‐9 suppresses vulnerable atherosclerotic plaque in acute coronary syndrome mice 9 . microRNA‐139‐5p (miR‐139‐5p) has been previously known as being aberrant regulated in some cardiac ischemia/reperfusion models 10 .…”
Section: Introductionmentioning
confidence: 99%